Alcohol and Short-Run Mortality: Evidence from a Modern-Day Prohibition - Kai Barron; Debbie Bradshaw; Charles D.H. Parry; Rob Dorrington; Pam Groenewald; Ria Laubscher; Richard Matzopoulos (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
On July 13, 2020 a complete nation-wide ban was placed on the sale and transport of alcohol in South Africa. This paper evaluates the impact of this sudden and unexpected five-week alcohol prohibition on mortality due to unnatural causes. We find that the policy reduced the number of unnatural deaths by 21 per day, or approximately 740 over the five-week period. This constitutes a 14% decrease in the total number of deaths due to unnatural causes. We argue that this represents a lower bound on the impact of alcohol on short-run mortality, and underscores the severe influence that alcohol has on society - even in the short-run.
Keywords: I18; I12; K42; 330; Alcohol; mortality; economics; health; South Africa; COVID-19; violence